Comparison Among QuinoloneMICs for Resistant Escherichia coli, S.aureusand P. aeruginosa - Rukhsana Firdous, Shabbir Ahmed, Ahson Ahmed. , (Journal of Rawalpindi Medical College, 2013)
Background: To compare the efficiency of second generation fluoroquinolones, i.e., ciprofloxacin, ofloxacin and enoxacin with third generation fluroquinolones, i.e, sparfloxacin . Method: Four fluoroquinolones(FQs), ciprofloxacin(CIP) enoxacin(ENX), ofloxacin(OFX), sparfloxacin(SPX) and three prevalent human pathogens were studied in clinical isolates of pus, urine and high vaginal discharge. Susceptibility to CIP, ENX, OFX and SPX was determined. These isolates were E.coli (203), S.aureus (194) and P.aeruginosa (106). From this pilot project the isolates which showed resistance to all FQs were chosen.The MICs of fluoroquinolones were determined by agar dilution method for these isolates.They were E.coli(n=79), S.aureus(n=34) and P.aeruginosa(n=20). The concentrations at which 50% and ,90% isolates were inhibited, (MIC50 & MIC90) were calculated. Also percentage of isolates inhibited at specific concentration of antibiotics was noted. Result. Lowest MICs were found by sparfloxacin (MIC50/ MIC90, E. coli > 64/512 μg/ml, S. aureus 64/ < 1024 μg/ml, P. aeruginosa = 64/256 μg/ml) and highest MICs, were of enoxacin among all the three isolates (MIC50/ MIC90 E. coli > 512 / < 2048 μg/ml, S. aureus 512/<2048 μg/ml. P. aerugionsa 512/>1024). Conclusion:Although the fluoroquinolones can be considered equivalent with regard to clinical susceptibility or resistance, fluoroquinolone MICs differ dramatically for fluoroquinolone-resistant because of differences in drug structure. Resistance was highest against enoxacin and was least against sparfloxacin. P. aeruginosa particularly showed low level of resistivity.